Tierra, territorio y autonomía: los gobiernos territoriales autónomos en la Amazonía Peruana - Balbuena Palacios, Patricia (2022)
Indigenous organizations were born out of the demand that, to this day, remains the backbone of their agenda: to protect their lands and natural resources, as a guarantees for their subsistence. The state response was to create the figure of “native community”, that would become fragment swarths of lowlands indigenous people’s territories; a legal figure similar to the “peasant community” in the Andes. To establish native communities, the state concentrates the indigenous population in villages, breaking traditional patterns of settlement. However, all these changes were accepted by indigenous organizations in exchange for protection against waves of immigration and illegal activities such as unauthorized logging.This article aims to show how the state response, through the legal framework of Native Communities Laws of 1974 and 1978, is no longer sufficient to fulfill the needs of indigenous peoples to protect their lands and territories. The native community’s regulation does not fulfill the standards developed by the Constitutional Court and the Inter-American Court of Human Rights, nor with the ILO Convention No 169. Illegal activities are growing in the Amazon, and conflicts due to territory overlaps are a permanent source of conflicts with formal or illegal third parties.In recent years, indigenous organizations have tried to recover the governance of their territories through two main strategies: i) titling as an indigenous people and no longer as communities; and ii) establishing autonomous governments on those territories. Currently, 7 indigenous peoples out of 51 have advanced in this pursuit. This process, led by the Wampis people, could be the beginning of a new stage in the relationship between the State and the traditional Amazonian inhabitants. The actors involved must urgently address the situation since what is at stake is the subsistence of indigenous peoples and the preservation of lowlands ecosystems and biodiversity. Meanwhile, illegal actors are taking advantage of these legal weaknesses to advance by leaps and bounds.